Methodology for adapting a co-created early childhood development intervention and implementation strategies for use by frontline workers in India and Guatemala: a systematic application of the FRAME-IS framework - Amruta Bandal; Sara Hernández; Revan Mustafa; Karyn Choy; Namrata Edwards; Magdalena Guarchaj; Marinés Mejía Alvarez; Anushree Sane; Scott Tschida; Chetna Maliye; Ann Miller; Abhishek Raut; et al. (Taylor & Francis Group, 2024)
There is little evidence on optimizing the effectiveness and implementation of evidence-based early childhood development (ECD) interventions when task-shifted to frontline workers. In this Methods Forum paper, we describe our adaptation of the International Guide for Monitoring Child Development (GMCD) for task-shifting to frontline workers in Guatemala and India. In 2021-2022, implementers, trainers, frontline workers, caregivers, and international GMCD experts collaborated to adapt the GMCD for a task shifted implementation by frontline workers. We used an eight-step co-creating process: assembling a multidisciplinary team, training on the existing package, working groups to begin modifications, revision of draft modifications, tailoring of visual materials and language, train-the-trainers activities, pilot frontline worker trainings, final review and feedback. Preliminary effectiveness of adaptations was evaluated through narrative notes and group-based qualitative feedback following pilot trainings with 16 frontline workers in India and 6 in Guatemala. Final adaptations included: refining training techniques to match skill levels and learning styles of frontline workers; tailoring all visual materials to local languages and contexts; design of job aids for providing developmental support messages; modification of referral and triage processes for children in need of enhanced support and speciality referral; and creation of post-training support procedures. Feedback from pilot trainings included: (1) group consensus that training improved ECD skills and knowledge across multiple domains; and (2) feedback on ongoing needed adjustments to pacing, use of video-based vs. role-playing materials, and time allocated to small group work. We use the Framework for Reporting Adaptations and Modifications to Evidence-based Implementation Strategies (FRAME-IS) framework to document our adaptations. The co-creating approach we use, as well as systematic documentation of adaptation decisions will be of use to other community-based early childhood interventions and implementation strategies.